(untitled) (BSAA arte, 2020)
In this article we will demonstrate the cross-cultural power of Japanese animation, as a medium that, thanks to the measures taken by the Japanese government, has achieved great international recognition in just few decades. After a review of the main dogmas prevailing in the country, Buddhism and Shintoism, we will relate many of the elements of Japanese folklore with various works of Japanese animation. Finally, we will delve into this union between animation and religion, customs and mythology, through a selection of anime films with international repercussions.